Bibliometric Analysis of Communities of Practice in the Field of Applied Social Sciences - Lima, Anderson Antônio; Ribeiro, Thiago de Luca Santana (Journal of Sustainable Competitive Intelligence, 2023)
Objective: the objective of the study is to analyze the theoretical conceptual evolution of the construct communities of practices in the field of applied social sciences and to identify the main existing theoretical currents and the frontiers of knowledge on the subject. phenomenon. Methodology/approach: this is a revisional study, elaborated through a bibliometric analysis, and this technique allows the mapping of the emergence and evolution of the concept of communities of practices (CoPs), including making it possible to identify the most cited/influential authors, authors' institutions and cooperation networks between authors. Originality/Relevance: an absence in the literature that allows identifying the emergence and evolution of the topic of communities of practice, as well as understanding the development of emerging themes and trends in future studies. Main conclusions: The bliometric review carried out in this study made it possible to identify the main theoretical bases that contributed to the formation of the knowledge domain of communities of practices (CoP's), as well as the current theoretical currents (borderline and emerging) that are the avenues of future studies about the theme. Theoretical/methodological contributions: The research findings contribute to the theoretical advancement of the topic, since with the identification of current emerging themes regarding communities of practice, new research can be developed to fill neglected gaps, in short revisional studies, such as bibliometrics and systematic reviews.